Membangun Kesadaran Finan Siswa Lewat Edukasi dan Sosialisasi di Sekolah - Surya Akbar; Riyan Pradesyah (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Independent Community Service Program (KKN) is a form of student community service that aims to apply knowledge practically in the field. This activity was carried out by students of the University of Muhammadiyah North Sumatra with the theme "Building Student Financial Awareness Through Education and Socialization in Schools. " This program aims to improve financial understanding among students from Elementary and High Schools in Perkebunan Gunung Melayu Village, Rahuning District, Asahan Regency. The methods applied include interactive socialization, educational games, and quizzes to stimulate students' interest and understanding of the importance of saving and managing finances from an early age. The results of this activity show that students begin to recognize the basic concepts of financial management, including how to distinguish between needs and desires, the significance of saving, and the application of Islamic financial principles in daily routines. In addition, this activity also serves to increase public understanding of the importance of financial education for children. The main element that facilitates the implementation of activities is support from educational institutions, village governments, and local communities, while the main challenge faced is the lack of attention of elementary school students caused by their habits that still prefer to play. Overall, this KKN program has a positive impact on increasing students' financial awareness and has the potential to be a simple financial education model at the elementary and secondary school levels